ANALISIS PEMANFAATAN KOLEKSI PERPUSTAKAAN MAN 8 JAKARTA BAGI PESERTA DIDIK KELAS X DAN XI TAHUN AJARAN 2024/2025 - Prio Bagas Wicaksono; Hendra Wicaksono; Agus Rifai (Pustabiblia: Journal of Library and Information Science, 2026)
School libraries can strategically assist learners in literacy and learning. However, student library collections often fall short. This study investigates how students in grades X and XI of Madrasah Aliyah Negeri (MAN) 8 in Jakarta used the library collection in the academic year 2024/2025. This research is crucial to evaluate the extent to which library collections fulfil students' information needs and assist them in the learning process. Descriptive quantitative method was used. Questionnaires were distributed to 84 respondents. The results of all valid and reliable items (Cronbach's Alpha = 0.760) indicated that the research instrument was valid and reliable. Five key metrics were used to analyse the data: ease of access, suitability of the collection, availability and promotion of information, information retrieval system, and service updates. The results showed that most students were satisfied with the library's opening times, its location, and whether the collections matched their studies. However, there were some shortcomings. These include the lack of promotion of new books, suboptimal utilisation of the computer catalogue, and the need for improved library programs and facilities. These findings show that students have utilised the library collection quite well. However, to enhance the library's role as a learning resource centre, improvements in promotion, digital services, and facilities development are needed.